Digital Expectations and Experiences in Education 2016
DOI: 10.1007/978-94-6300-648-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Harassment and Quality of Life1

Abstract: Research on bullying and harassment in Scandinavia has been going on for several decades, and is appearing in new frameworks and forms since the new categories of "cyber harassment" or "cyberbullying" has been introduced. Bullying is a phenomenon of great importance, as it seems to affect persons negatively in their everyday functioning. We designed a questionnaire on cyber harassment, which was answered by pupils, at five schools in Tromsø (N=878). This questionnaire included a section of questions concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…Results from analysis of the entire WiT project period suggested that the prevalence of both traditional and digital bullying decreased year by year. In the first year of the study 10.4% reported being bullied either traditional or digital 46 . In 2017 the prevalence had dropped to 8.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Results from analysis of the entire WiT project period suggested that the prevalence of both traditional and digital bullying decreased year by year. In the first year of the study 10.4% reported being bullied either traditional or digital 46 . In 2017 the prevalence had dropped to 8.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Gangguan adalah satu bentuk pencerobohan tingkah laku (Fernandez et al 2015). Kewujudan teknologi Internet dan media sosial telah membentuk gangguan teknologi yang dikenali sebagai gangguan siber (Thorvaldsen et al 2016). Pelaku gangguan siber bersifat lebih agresif kerana identiti mereka tidak diketahui (Coyne et al 2017;Thorvaldsen et al 2016).…”
Section: Ulasan Kajian Lepas Gangguan Siberunclassified
“…Kewujudan teknologi Internet dan media sosial telah membentuk gangguan teknologi yang dikenali sebagai gangguan siber (Thorvaldsen et al 2016). Pelaku gangguan siber bersifat lebih agresif kerana identiti mereka tidak diketahui (Coyne et al 2017;Thorvaldsen et al 2016). Gangguan siber adalah keadaan di mana mangsa diganggu, diancam dan dimalukan dengan niat jahat (Alhujailli & Karwowski 2018) sama ada sekali atau berulang kali dan mangsa tidak mampu untuk mempertahankan diri sendiri (Coyne et al 2017;Gardner, et al 2016;Thorvaldsen et al 2016)…”
Section: Ulasan Kajian Lepas Gangguan Siberunclassified
See 1 more Smart Citation
“…Both bullying victimization and harassment are forms of adversity of great distress, which negatively affect mental health and quality of life in both short and long term (Allison, Roeger & Reinfeld‐Kirkman, 2009; Branwhite, 1994). In Norway close to 30% rapport harassment, 6–10% report bullying at school, and up to 6% report digital bullying (Bakken, 2021; Forsberg & Thorvaldsen, 2022; Thorvaldsen, Stenseth, Egeberg, Pettersen & Rønning, 2016).…”
Section: Introductionmentioning
confidence: 99%